DESAIN DAN IMPLEMENTASI COMPANY PROFILE BERBASIS WEB MENGGUNAKAN ADOBE FLASH 8.0 PADA RJS DIGITAL PRINTING - Oktandia Cahyo Widodo; Dwi Safiroh Utsalina (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
Interactive multimedia is widely used to make the company profile, animation, games, sketches and others. The author chose an interactive company profile because on Information Technology, an interactive multimedia become a trend for many companies and other institutions as a visualization media profile, the work result and their files. one of Multimedia functions is the media to give information. Its to promote some goods or services to another company. RJS Digital Printing is a company engaged in the field of company printing. many products have generated by company printing, now RJS Digital Printing is growing in their business. Therefore, to maintain existing customers and new customers, we need a media that can introduce the capacity and quality of the company to the businessman to make a cooperation in the digital printing. After analyzing the problems of digital printing, the authors has an initiative to create a company profile, it is an interactive web that used to make a cooperation with another company. Hopefully, by using this strategy would make a company to be grow up and would minimize a promosition costs.